2002
DOI: 10.1016/s0378-1097(01)00505-5
|View full text |Cite
|
Sign up to set email alerts
|

Presence of organic sources of nitrogen is critical for filament formation and pH-dependent morphogenesis in Yarrowia lipolytica

Abstract: Yeast dimorphism is an attractive model for the study of cell morphogenesis and differentiation. The non-conventional yeast Yarrowia lipolytica was chosen to characterise the regulation of dimorphic transition by extracellular pH and by the presence of organic sources of nitrogen. Organic nitrogen sources appear to be required for the morphogenic effect of pH. Two sets of mutants defective in either pHdependent or nitrogen source-dependent signalling pathway were analysed. The results suggest that the latter b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…This indicated a dependence on respiration and a healthy metabolic state for mycelia formation. It has been proposed that filament formation requires more energy and larger amounts of carbon and nitrogen as building blocks (Szabo and Stofanikova, 2002). Thus, under nutrient limitation, the yeast form of Y. lipolytica predominates.…”
Section: Discussionmentioning
confidence: 99%
“…This indicated a dependence on respiration and a healthy metabolic state for mycelia formation. It has been proposed that filament formation requires more energy and larger amounts of carbon and nitrogen as building blocks (Szabo and Stofanikova, 2002). Thus, under nutrient limitation, the yeast form of Y. lipolytica predominates.…”
Section: Discussionmentioning
confidence: 99%
“…In common with a Ylrim101⌬ allele, pal mutations affected mating efficiency and sporulation, although the YlRim101p requirement appeared to be more stringent (69) (see below). In contrast to Saccharomyces, pal mutations do not prevent invasiveness (124); in contrast to Candida, they do not impair hyphal formation (although hyphal branching frequency is increased) (56,120,124). Recent data (120) strongly suggest that the known pH dependency of the transition from the yeast to the hyphal mode of growth in Yarrowia reflects the indirect control by ambient pH of the availability of organic nitrogen sources in complex media, which would explain the absence of morphogenetic defects resulting from pH-regula- (56).…”
Section: Mutations In Pal Genesmentioning
confidence: 99%
“…As predicted by the PacC model, a null Ylrim101⌬ mutation leads to acidity mimicry. Like pal Ϫ mutations, Ylrim101⌬ prevents the expression of both the acidic and the alkaline protease genes, impairs growth at alkaline pH, and has no effect on invasiveness and only a minor effect on hyphal formation (56,69,120).…”
Section: Mutations In Ylrim101mentioning
confidence: 99%
“…Dimorphic transition is a wellknown phenomenon for Y. lipolytica, but the exact causes of induction remain unclear [27,28]. The most probable cause for dimorphic transition in Y. lipolytica has been attributed to pH change [29], and this fact has been validated in our previous work [8]. The environmental conditions met by cells in the foam phase have not been characterized in the present study, but it seems that dimorphic transition could explain the segregation reported at the level of the flow cytograms in the case of the MFMoperated cultures.…”
Section: Resultsmentioning
confidence: 99%
“…The environmental conditions met by cells in the foam phase have not been characterized in the present study, but it seems that dimorphic transition could explain the segregation reported at the level of the flow cytograms in the case of the MFMoperated cultures. The impact of dimorphism on lipase synthesis is not well understood at this time, but it seems that this physiological change induces a drop at the level of the lipase yield [26][27][28][29]. Further studies are thus needed to address these phenomena.…”
Section: Resultsmentioning
confidence: 99%